David Samuel Margoliouth’s views on the Prophethood (p.b.u.h) and revelation of the Qur’an: a critical assessment - Muhammad, Akilu Aliyu; Abdul Rahim, Adibah (IIUM Press, International Islamic University Malaysia, 2017)
The Prophethood of MuÍammad (p.b.u.h) and revelation of the Qur’Én have been the main themes in Muslim-Christian relations. Many works were and are published by Christian scholars regarding these issues. David Samuel Margoliouth (d. 1940) is one of the most prominent and intellectual Christian scholars who wrote extensively on these subjects. His works are amongst the most controversial treatises which depicted Prophet MuÍammad (p.b.u.h) and the revelation of the Qur’Én negatively. Researches on his views concerning these issues seem to be more descriptive than analytical and evaluative. Hence, in this research, a new and unique approach has been applied. The researcher has attempted, while investigating his evidence, to critically analyse and assess his various views concerning these areas. In an attempt to carry out this task, principal approaches, namely historical, analytical, evaluative and comparative have been widely used. Thus, after presenting a considerable account on his historical and intellectual backgrounds, the researcher has analysed his various views where Margoliouth has been found depicting the Prophet (p.b.u.h) as a superstitious, idolater, craven, immoral and even as a false Prophet whose main aim was to gain abslute power and personal distinction. Moreover, as regard to the the Qur’Én, Margoliouth has been found depicting the Prophet’s experiences during its reception as epileptic fits. He has also been found attempting to figure out some difficulties or problems in it. However, evaluation of those and his other views has revealed that, he was a mere conjecturer since all his evidence could not withstand critical examinations.